La perception de l’accompagnement en entreprise par les apprenti-e-s et son influence dans la transmission des savoirs pratiques de métier. Le contexte de la formation en alternance en maçonnerie en Suisse - Isabelle Caprani; Kerstin Duemmler; Alexandra Felder (Éducation et Socialisation)
In-company coaching implies support and supervision of apprentices in working situation enabling them to familiarize themselves with the various techniques of work. This is particularly evident in the social relations between apprentices and supervisors and people in charge of their training. Based on interviews with bricklaying apprentices, we study the influence of support on the occupational development of young people in training. Our approach allows to identify which support practices contribute to apprentices’ occupational development and which ones can hinder it. The challenge for in-company coaching resides in assigning responsibilities to the various team members and in creating a collective support adapted to the professional needs of apprentices.